Petrale sole transboundary connectivity and settlement success: a biophysical approach - Santa Cruz, Francisco; Parada, Carolina; Haltuch, Melissa; Wallace, John; Cornejo-Guzmán, Sebastián; Curchitser, Enrique (Frontiers in Marine Science, 2023)
Connectivity between inferred spawning areas and potential settlement areas of the petrale sole (Eopsetta jordani) was explored in the California Current System (CCS) using an individual-based model (IBM) coupled with the ROMS hydrodynamic model for the period 1988-2008. The IBM modeled pelagic early life stages, including egg and larval development, growth, natural mortality and settlement into benthos. Eggs were released within discrete spawning grounds identified from the winter fishery logbook data. Potential settlement areas were defined based on bathymetrical criteria and juvenile (2-year old) distribution from a groundfish bottom trawl survey. The influence of cross-shelf and alongshore advection on the transport and connectivity between spawning and benthic settlement areas was explored by identifying the location of juveniles (22 mm length) among the potential settlement areas. The most important spawning regions varied over time with between 4 and 19% of spawned individuals successfully settling, mostly ranging from off northern Washington to northern Oregon. The strong influence of northward alongshore transport resulted in transboundary transport of pelagic life stages from U.S. spawning grounds to inner shelf settlement areas in Canadian waters, with 33.9-70.4% (average 49.7 ± 9.6) of annual successful juveniles settling in Canada. Interannual variability in juvenile settlement success suggests that mesoscale (100-200 km) oceanographic structures play a major role defining pelagic juvenile transport trajectories. While, in some years, the presence of coastal cyclonic eddies can retain juveniles off Oregon, the strong northward transport supplies a large number of juveniles to Moresby and Vancouver island, clearly showing that petrale sole off the west coast of North America are a transboundary stock with important settlement areas off the coast of British Columbia, thus extension of this study into Canadian waters is particularly relevant.